Analysis and Design of Web-based Information System for Coffeeshop Management using Design Thinking Methodology: Case of Kopi KurangLebih - Gilberto Dennis G E Sidabutar; Jesslyn Alvina Seah; Yerik Afrianto Singgalen (Universitas Bina Darma, 2023)
The traditional approach to Coffeeshop business requires business owners to manually record orders and purchase transactions, which poses serious challenges to service management in terms of effectiveness and efficiency. To optimize Kopi KurangLebih Coffeeshop needs and increase its appeal to consumers, a relevant management information system is required. Solving business problems requires web-based information systems that facilitate the ordering and purchasing process. In this study, we use design thinking methodology to design a system that meets user needs. Kopi KurangLebih users are buyers, stakeholders, customers, baristas and cashiers. The Kopi KurangLebih website has several advantages, including viewing menus and ratings, food and drink selections, promotions of the day, points redeemable for various user benefits, and other facilities within the cafe. Therefore, Kopi KurangLebih can make information readily available to purchasers and potential purchasers to increase its attractiveness and marketability. The results of this study show that the Coffeeshop management system design supports Coffeeshop management processes more efficiently and effectively compared to traditional business processes. Nonetheless, the role of each actor in performing their respective tasks optimally becomes a determinant of business losses and gains.